Hierarchically Structured DNA‐Based Hydrogels Exhibiting Enhanced Enzyme‐Responsive and Mechanical Properties. (16th September 2020) - Du, Xiaoxue; Bi, Yanhui; He, Pingping; Wang, Chunyan; Guo, Weiwei
Abstract: Programmable stimuli‐responsive materials have great potential in biosensing and biomedical applications. However, the slow response of DNA hydrogels to biological targets, especially bio‐macromolecules, i.e., proteins, due to the slow mass transfer within hydrogel matrices, as well as poor mechanical strength, severely hinders their extensive applications. Herein, the construction of hierarchically structured DNA hydrogels exhibiting significantly enhanced responsive and mechanical properties via a facile cryostructuration process is demonstrated. During the cryostructuration, interconnected macropores that can function as the channels for the migration of bio‐macromolecular substances, i.e., enzymes, are formed with the generated ice crystals as templates; meanwhile, densely crosslinked networks between the macropores are formed by the concentrated monomers localized in the unfrozen zones of the gelation system, leading to higher strength of the gel matrices. By programming the sequences of the DNA crosslinkers, two model hydrogels composed of enzyme‐responsive DNA structures and catalytic DNA crosslinking structures that can collaborate with enzymes to form biocatalytic cascades are constructed, and, in both systems, the hierarchically structured DNA hydrogels exhibit significantly enhanced responsive properties and mechanical strengths compared with typical DNA hydrogels. Moreover, the introduction of thermosensitive polymers can further endow the system with thermally switchable responsive properties. Abstract : Responsive DNA hydrogels with hierarchically porous structures are developed via cryostructuration, and exhibit significantly enhanced responsive properties to external stimuli, such as to enzymes, and enhanced mechanical properties compared to typical DNA hydrogels. Furthermore, by introducing thermosensitive polymers, temperature controlling the responsive properties of the cryogel systems can be achieved.